Performance Based Teacher Education: The Case Against Its Wholesale Use - Newcomb, L.H. (Journal of Agricultural Education, 1983)
The notion of performance-based teacher education has been discussed by professors of agricultural education for more than a decade now. Yet, here we are examining it anew. What we must come to realize, sooner or later, is that PBTE falls short of the once hailed promises and expectations because it contains fundamental flaws.